Sex differences in human fatigability: Mechanisms and insight to physiological responses - Hunter, S. (Acta Physiologica, 2014)
Sex-related differences in physiology and anatomy are responsible for profound differences in neuromuscular performance and fatigability between men and women. Women are usually less fatigable than men for similar intensity isometric fatiguing contractions. This sex difference in fatigability, however, is task specific because different neuromuscular sites will be stressed when the requirements of the task are altered, and the stress on these sites can differ for men and women. Task variables that can alter the sex difference in fatigue include the type, intensity and speed of contraction, the muscle group assessed, and the environmental conditions. Physiological mechanisms that are responsible for sex-based differences in fatigability may include activation of the motor neuron pool from cortical and subcortical regions, synaptic inputs to the motor neuron pool via activation of metabolically-sensitive small afferent fibres in the muscle, muscle perfusion, and skeletal muscle metabolism and fibre type properties. Non-physiological factors such as the sex bias of studying more males than females in human and animal experiments can also mask a true understanding of the magnitude and mechanisms of sex-based differences in physiology and fatigability. Despite recent developments, there is a tremendous lack of understanding of sex differences in neuromuscular function and fatigability, the prevailing mechanisms and the functional consequences. This review emphasises the need to understand sex-based differences in fatigability in order to shed light on the benefits and limitations that fatigability can exert for men and women during daily tasks, exercise performance, training and rehabilitation in both health and disease.